A novel electrochemical aptamer–antibody sandwich assay for lysozyme detection. Issue 12 (21st June 2015) - Ocaña, Cristina; Hayat, Akhtar; Mishra, Rupesh; Vasilescu, Alina; del Valle, Manel; Marty, Jean-Louis
<x xml:space="preserve">Abstract</x> In this paper, we have reported a novel electrochemical aptamer–antibody based sandwich biosensor for the detection of lysozyme.